The quasars’ redshift estimation method based on piecewise Gaussian fitting - Yanrui Su; Li Zhang; Bin Jiang; Jiaqi Liu; Fabao Yan (International Journal of Distributed Sensor Networks)
To solve the problem that high-redshift and broad emission lines weaken the quasar discovery and observation severely, a new redshift calculation method based on piecewise Gaussian fitting is proposed. The denoised and normalized spectrum is divided into two regions, peak and non-peak, by mean square error threshold segmentation first. Then, the non-peak region spectrum is applied to fit the continuous spectrum, removal of which gains access to the residual spectrum. And, the peak of each segment in the residual spectrum is precisely fitted by single-peak Gaussian fitting to replace the original multi-peak Gaussian fitting. Finally, through matching the accurate peak value with the stationary template, the redshift value is acquired. Compared with traditional methods, the method proposed improves the precision of continuous spectrum fitting and redshift calculation. The effectiveness and accuracy of this method have been verified by experiments based on the Sloan Digital Sky Survey data.